SIMPLIFIED COMPUTATION METHODOLOGY FOR CONTACT FORCES ON TAPERED ROLLING BEARING WITH FLEXIBLE PARTS - Alžbeta SAPIETOVÁ; Pavol NOVÁK; Peter ŠULKA; Milan SAPIETA; Lenka JAKUBOVIČOVÁ (Scientific Journal of Silesian University of Technology. Series Transport)
Durability calculations of bearings take in account the distribution of forces on rollers. Calculation of these forces in flexibly supported rings is the aim of the paper. We use simplified finite element (FE) models of bearings, which are integrated into the external geometry. This approach can consider the stiffness of the surrounding structure as well as the clearance of the bearing rings, the misalignment of bearings, shaft deflections, and the forces of crowning rollers. The presented results show an influence of the initial radial interference of the outer ring with housing on the distribution of forces in bearing rollers. As the radial stiffness of the housing is close to the stiffness of the outer ring interference, this causes considerable deformation of the housing. The presented approach is also able to calculate the distribution of contact pressures over any rolling element.